How exercise shapes the anti-inflammatory environment in multiple sclerosis – a conceptual framework focusing on tryptophan-derived molecules in T cell differentiation - Wences Chirino Tiffany Y.; Joisten Niklas; Zimmer Philipp; Proschinger Sebastian (Translational Exercise Biomedicine)
Multiple Sclerosis (MS) is a chronic neuroinflammatory autoimmune characterized by inflammation-induced lesion formation after immune cell infiltration into the central nervous system. T cells play an intriguing role in MS immunopathology and research over the past decade has shown that tryptophan (TRP)-derived metabolites are crucial molecules affecting T cell differentiation, also in MS, and are modulated by exercise. The aryl hydrocarbon receptor (AHR), for which TRP metabolites are well-known ligands, has been elucidated as main driver of T cell differentiation and an enhanced anti-inflammatory cellular milieu in human MS and preclinical mouse models. By integrating evidence from different research fields, the aim of this article is to summarize and critically discuss the potential of exercise to activate the AHR in T cells by modulating circulating TRP-derived metabolites and to provide a conceptual framework on potential benefits in MS immunopathology.